ЖАНГОВОР ЧОРЛОВ ВОСИТАЛАРИ ТУШУНЧАСИ ВА УНИНГ ИЛМИЙ- НАЗАРИЙ ТАҲЛИЛИ ("XXI ASRDA INNOVATSION TEXNOLOGIYALAR, FAN VA TAʼLIM TARAQQIYOTIDAGI DOLZARB MUAMMOLAR" nomli respublika ilmiy-amaliy konferensiyasi, 2024)
Although a lot of research has been done in the military field, the concept of combatvehicles has not yet been comprehensively explored. This article describes the results ofscientific research conducted in this directio